An Islāmic Perspective of Justice Between the Employer and Employee - Azeez, Rasheed Olalekan; Miftaudeen, Rabiu (Jurnal Pembelajaran dan Ilmu Pendidikan, 2024)
Al-‘Adl (justice), in its actual sense, encompasses treating living and non-living in a fair, equitable and just manner. It is a tool that Islām uses to set everything accordingly as Allah commanded everyone to act justly. Justice is expected from all aspects of life including the workforce. However, the Muslims who are expected to show living examples of justice are seen in this contemporary world with the acts of injustice in their workplace as employers and employees. The paper explained the application of justice between employer and employee focusing on exploring how Islāmic teachings guide this relationship. The paper used an analytical research method. This method was used to explain the expectations of Islām from the employers and employees. The paper revealed that both the employers and employees lag in what is expected from them. That is, the employers and employees fail to meet up with the rules and regulations set by Islām concerning the rights between employers and employees. The paper concludes that the workforce will be facing problems if it fails to include fairness, equity, morality and respect in its watchbook. It was recommended that employers and employees cling to Allah's commandments for setting an ethical workforce and equitable work environments in contemporary society.